Production of lipopolysaccharide-induced tumour necrosis factor during influenza virus infection in mice coincides with viral replication and respiratory oxidative burst - K. N. Masihi; H. Hintelmann; K. Madaj; G. Gast (Hindawi Limited, 1995)
Increased morbidity and mortality occur regularly during influenza epidemics. The exact mechanisms involved are not well defined but bacterial superinfection of influenza virus infected patients is considered to play an important role. In the present study, the effect of influenza virus infection on in vivo production of turnout necrosis factor (TNF) in response to bacterial stimuli was investigated. Release of TNF in mice infected by an aerosol of influenza virus was significant after administration of bacterial lipopolysaccharide (LPS) at 72 h, whereas administration of homologous influenza virus produced only modest amounts of TNF at 96 h. Significant production of TNF was observed 48 h after intravenous administration of infectious influenza in response to LPS but not with the homologous virus. TNF induced after influenza virus infection could be blocked by a specific murine anti-TNF monoclonal antibody. Higher TNF production following aerosol influenza infection correlated with peak titres of influenza virus in the lungs of infected mice and with enhanced generation of luminoldependent chemiluminscence.